PENDEKATAN PENGKAJIAN AGAMA: ANTROPOLOGIS - Hannym Finadiya Himatul Aliyah; Salsabila Ibnati Maelya; Maftuh Ajma’in (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The anthropological approach in the study of religion is one of the methods used to understand religion as a social and cultural phenomenon in human life. This approach emphasizes that religion is not only understood as a theological belief system, but also as a social practice influenced by traditions, culture, and the surrounding community environment. Through an anthropological perspective, the study of religion is conducted by observing religious rituals, symbols, and patterns of behavior in how communities practice their religious teachings. Therefore, this approach helps explain how religion interacts with culture and shapes social values within society. In Islamic studies, the anthropological approach can be used to understand various religious practices that develop among Muslim communities, including the influence of local traditions on these practices. This approach provides a more comprehensive understanding of the relationship between religion, culture, and human social life in various social contexts.